2021
DOI: 10.1016/j.jtrangeo.2021.103191
|View full text |Cite
|
Sign up to set email alerts
|

The impact of Covid-19 on children's active travel to school in Vietnam

Abstract: This is among the first studies to provide empirical evidence on active school travel rates and determinants before and after the first Covid-19 lockdown in spring 2020. We have collected and analyzed primary survey data on the school travel patterns of 472 school-age children in Hanoi, Vietnam. The findings show that the Covid-19 pandemic has been quite detrimental: once schools reopened, the prevalence of active school travel decreased from 53% to less than 31%. Where parents, especially mothers, did not fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…Most use discounted monthly passes, which are quite affordable. 1 While the overall bus modal share in the Vietnamese capital is only 7–9 percent (Department of Transport 2021 ; Nguyen et al 2020 , 2021b ; TRAMOC 2019 ), student passengers account for more than a third of bus trips (Nguyen et al 2017 ). Their contribution to public transport patronage became clearer in 2020 at the outset of the Covid-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most use discounted monthly passes, which are quite affordable. 1 While the overall bus modal share in the Vietnamese capital is only 7–9 percent (Department of Transport 2021 ; Nguyen et al 2020 , 2021b ; TRAMOC 2019 ), student passengers account for more than a third of bus trips (Nguyen et al 2017 ). Their contribution to public transport patronage became clearer in 2020 at the outset of the Covid-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Automobile ownership is low but on the rise; it currently stands at 60 cars per 1000 inhabitants. 2 Cycling is a marginal mode, mainly used by children; adults mostly consider it as recreation (Hansen 2017 ; Nguyen et al 2021a ).…”
Section: Introductionmentioning
confidence: 99%
“…The full-text screening was undertaken for 31 articles. Eight papers informed the assessment of six indicators: Overall Physical Activity , 15 , 16 , 17 Active Play , 16 Active Transportation , 18 Sedentary Behaviors , 15 , 17 , 19 Family and Peers , 20 and Community and Environment . 21 , 22 Grey literature searches resulted in three government strategic plans reporting on two indicators: School 23 , 24 and Government 25 ; the Global School-based Health Survey (GSHS) report 6 which informed both Overall Physical Activity and Active Transport , and another report by Department of Preventive Medicine, which provided data to assess the Family and Peers indicator.…”
Section: Resultsmentioning
confidence: 99%
“…6 Another cross-sectional study in 2020 reported that 53% of school children (aged 5–15 years) used active transport to and from school in Hanoi city; however, this proportion reduced to only 16% during the COVID-19 pandemic. 18 Although this data were only collected in Hanoi, this is the second-largest city in Viet Nam and the study findings are likely generalizable to other urban areas. In other provinces and rural areas, it is more common for students to walk or bike to school due to limitations in other modes of transportation.…”
Section: Discussionmentioning
confidence: 96%
“…The authors worked with bus providers from September to December 2020 to collect the collision data of subsidized bus routes in Hanoi from 2015 to 2019. The data of 2020 were excluded since the bus operation within this period were largely affected by the social distancing directive mandated to stop the transmission of COVID-19 [49][50][51][52].…”
Section: Data Collectionmentioning
confidence: 99%